Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 204344 by SEKRET last updated on 13/Feb/24

            ctg^6 ((π/9))−9∙ctg^4 ((π/9))+11∙ctg^2 ((π/9))=?

ctg6(π9)9ctg4(π9)+11ctg2(π9)=?

Commented by SEKRET last updated on 14/Feb/24

  solution

solution

Commented by Frix last updated on 14/Feb/24

(1/3)

13

Answered by Frix last updated on 15/Feb/24

Not as hard as it looks...  x=cot^2  (π/9)  c=x^3 −9x^2 +11x  x=t+3  z=t^3 −16t−21  t=x−3=cot^2  (π/9) −3=((2−4cos ((2π)/9))/(cos ((2π)/9) −1))=((2−4c)/(c−1))  z=t^3 −16t−21=−((21c^3 +c^2 −17c+3)/(c^3 −3c^2 +3c−1))  c^3 =cos^3  ((2π)/9) =((6cos ((2π)/9) −1)/8)=((6c−1)/8)  z=−((((21(6c−1))/8)+c^2 −17c+3)/(((6c−1)/8)−3c^2 +3c−1))=  =−((c^2 −((5c)/4)+(3/8))/(−3c^2 +((15c)/4)−(9/8)))=(1/3)

Notashardasitlooks...x=cot2π9c=x39x2+11xx=t+3z=t316t21t=x3=cot2π93=24cos2π9cos2π91=24cc1z=t316t21=21c3+c217c+3c33c2+3c1c3=cos32π9=6cos2π918=6c18z=21(6c1)8+c217c+36c183c2+3c1==c25c4+383c2+15c498=13

Terms of Service

Privacy Policy

Contact: info@tinkutara.com